Analisis Kualitas Produk Minyak Goreng Kemasan Standing Pouch (STP) Menggunakan Metode FMEA pada PT. XYZ - Fernandi, Muhammad Ramadhan; Risqi, Akhmad Wasiur; Negoro, Yanuar Pandu (Jurnal Serambi Engineering, 2022)
This research was conducted with the number of product defects that occur in the production process of making Standing Pouch packaged cooking oil, this study also aims to reduce product defects using the FMEA method. In this study using qualitative data where the data is from the results of questionnaires with influential sources in the production process. In this study, there are 5 models that cause product defects, including leaky pouches, unclear date numbers, broken seals, damaged cartons, less oil volume. The FMEA method itself has 3 tools used to assist in completing this research, namely Pareto diagrams, flowcharts, and fishbone diagrams, where the 3 tools aim to get results to determine the RPN value or the highest value, the RPN value itself is obtained from the multiplication result. between severity, occurrence, and detection. From the results of the research conducted, it was found that the cause of the defect in standing pouch cooking oil packaging products with the highest RPN value. The conclusions obtained are the pouch is leaking (pierced by a sharp object when in the machine or conveyor), the date number is not clear (the pouch is not hot enough so that when clamped the embossed pouch is still hard), the seal is broken (the sealbar heater setting is not right), the carton is damaged (the slotter has more visibility). 0.6mm so that it is exposed to cardboard when gluing the insulation, the volume of oil is less (the crank setting is not right).